Specific detection of small ruminant lentiviral nucleic acid sequences located in the proviral long terminal repeat and leader-gag regions using real-time polymerase chain reaction - Brinkhof, J.M.A.; van Maanen, C.; Wigger, R.; Peterson, K.; Houwers, D.J. (Journal of virological methods, 2008)
Real-time polymerase chain reaction (RT-PCR) detection of proviral nucleic acid sequences of small ruminant lentiviruses (SRLV) in blood samples was developed and evaluated. Priming oligonucleotides were designed on the highly conserved 5′ untranslated leader-gag region while those on the long terminal repeat (LTR) assay were derived from literature. DNA was extracted from the buffycoat interlayer of centrifuged blood samples. Real-time PCR was performed by means of LightCycler technology (Roche Applied Science) using melting temperature analysis (SYBR Green I) for detection. Results were compared with those of serology using samples from Dutch sheep and goat flocks with known SRLV statuses, with sequential samples from a natural transmission experiment and samples from different regions in Norway, France, Spain and Italy. Real-time PCR testing, especially the application of oligonucleotides for priming the leader-gag region appeared promising in detecting SRLV specific proviral DNA in blood samples from both sheep and goats.